Metal-contaminated resuspended sediment particles are a minor metal-uptake route for the Sydney rock oyster (Saccostrea glomerata) — A mesocosm study, Sydney Harbour estuary, Australia. Issue 1 (15th March 2016) - Lee, J.-H.; Birch, G.F.; Simpson, S.L.
Abstract: Resuspension of surficial sediments is considered a key process influencing bioaccumulation of metals in filter-feeders in the contaminated Sydney Harbour estuary (Australia). However, previous investigations were unable to establish a significant relationship between metals in sediments or suspended particulate matter (SPM) and oyster tissue concentrations. This study used a 60-d laboratory mesocosm experiment to expose Sydney rock oysters, Saccostrea glomerata, to a natural range of SPM concentrations with different SPM-metal concentrations. Dissolved metal concentrations were low and the availability of algae provided as food was constant for all treatments. Tissue metal concentrations of Cu, Pb and Zn increased significantly, however, no relationship was determined between tissue metal concentrations in the oyster and either SPM or SPM-metal concentrations. The results indicated that exposure to resuspended contaminated sediment particles contributed little to the observed metal uptake. Dissolved or algae food sources appear to be more important for metal accumulation in these oysters. Highlights: Oysters possessed significantly greater Cu and Zn concentrations after 60 days. No relationship was observed for SPM or SPM-metal concentrations to oyster metals. Excess SPM did not lead to higher oyster tissue metal concentrations. Dissolved and algae food sources may be more important metal exposure routes.